Periodontal and Inflammatory Effects of Switching to Combustion-Free Nicotine Delivery Systems: A 12-Month Randomized Controlled Trial - Amaliya Amaliya; Ira Citra Afsari; Prajna Metta (The ASEAN Journal of Military and Preventive Medicine, 2026)
Introduction: Tobacco smoking is a recognized risk factor for periodontal disease, contributing to inflammation and poor oral health. Combustion-free nicotine delivery systems (C-F NDS) have emerged as alternatives, yet their long-term clinical implications on periodontal health remain unclear. Objective: This study aimed to assess the 12-month effects of switching from conventional smoking to C-F NDS on cigarette consumption, gingival inflammation, plaque accumulation, and exhaled carbon monoxide (CO) levels. Methods: A randomized controlled trial was conducted with 40 adult smokers, allocated into two groups: one continued smoking conventional cigarettes, and the other transitioned to C-F NDS (IQOS™ or RELX™). Variables measured included cigarettes per day (CPD), Modified Gingival Index (MGI), plaque accumulation scores (R30, R120, Simple OH Score) using Quantitative Light Fluorescence (QLF) technology with Qraycam , and CO levels. Data were analyzed using parametric and non-parametric tests with significance at p < 0.05. Results: The C-F NDS group showed a significant reduction in CPD (p < 0.0001), and lesser progression of gingival inflammation (MGI Δ: 0.94 vs. 1.25; p = 0.041). Reductions were also observed in early plaque (R30, p = 0.046) and oral hygiene scores (Simple OH Score, p = 0.026). CO levels declined in both groups, with a greater reduction among C-F NDS users (ΔCO: -5.65 ppm vs. -4.25 ppm), although not statistically significant (p = 0.621). Conclusion: Switching to C-F NDS is associated with reduced cigarette use, improved periodontal markers, and decreased exposure to combustion-related toxins. These findings support the inclusion of C-F NDS in harm reduction strategies for tobacco users.